HOXA6 inhibits cell proliferation and induces apoptosis by suppressing the PI3K/Akt signaling pathway in clear cell renal cell carcinoma - Wu, Feixiang (Int J Oncol, 2019)
Clear cell renal cell carcinoma (ccRCC) is the most common type of renal cell carcinoma and the incidence of this disease is increasing. The present study aimed to investigate the role of homeobox A6 (HOXA6) in the proliferation and apoptosis of ccRCC cells. Analysis of the GSE6344 dataset and immunohistochemistry revealed that the mRNA and protein expression levels of HOXA6 were suppressed in ccRCC tissues. To evaluate the roles of HOXA6 in cell proliferation and apoptosis, ccRCC cell lines (786-O and 769-P) were transfected with plasmids expressing HOXA6, empty vector, short hairpin (sh)HOXA6 and non-targeting shRNA (NC). Cell Counting Kit-8, colony formation and 5-ethynyl-2′-deoxyuridine staining assays were performed to analyze cell proliferation. In addition, Caspase-Glo and terminal deoxynucleotidyl transferase dUTP nick end labeling assays were performed to detect apoptosis. Furthermore, the cell cycle and apoptotic rates of 786-O and 769-P cells were analyzed by flow cytometry. The results demonstrated that, compared with the empty vector group, the proliferation of 786-O and 769-P cells decreased following HOXA6 overexpression; however, compared with the NC group, cell proliferation increased in the shHOXA6 group. The rate of apoptosis of HOXA6-overexpressing cells was increased compared with the empty vector group, while the rate of apoptosis in the shHOXA6 group was reduced compared with the NC group. In addition, flow cytometry demonstrated that upregulated HOXA6 expression levels could inhibit the cell cycle at the G(0)/G(1) phase. Western blotting revealed that the expression levels of phosphoinositide 3-kinase (PI3K), phosphorylated (p)-protein kinase B (Akt), mitogen-activated protein kinase kinase, p-extracellular signal-regulated kinase (ERK) and B-cell lymphoma 2 (Bcl-2) were suppressed in cells overexpressing HOXA6; however, the protein expression levels of phosphatase and tensin homolog, Bcl-2-associated X protein, cleaved caspase-3 and cleaved-poly (ADP-ribose) polymerase were increased compared with the empty vector group. Opposing results were reported for the shHOXA6 group compared with the NC group. In summary, the results demonstrated that HOXA6 suppresses cell proliferation and promotes apoptosis, which may occur via inhibition of the PI3K/Akt/ERK cascade. These findings indicate the role of HOXA6 in ccRCC; however, the underlying mechanism requires further investigation.